Pangan Berkelanjutan dalam Wadah - Sutaman, Sutaman; Fithor, Alin; Suyono, Suyono; Baihaqi, Ahmad Fauzan (Maslahah: Jurnal Pengabdian Masyarakat, 2025)
Containerized fish farming is an innovative applied technology developed to address land limitations and improve food security and household economic well-being. This technology is simple, low-cost, space-efficient, and easy to implement in domestic environments, making it highly suitable for both urban and densely populated areas. This system utilizes water optimally and can be combined with plant cultivation through a simple aquaponics concept, thereby reducing waste and increasing the efficiency of integrated and sustainable space utilization. The result of this community service activity is the implementation of containerized fish farming technology, which serves as a suitable solution for urban and densely populated communities to support nutritional needs and supplement family income. Farmed fish also serve as an essential source of animal protein to support household nutritional security. However, in practice, limited space, high population density, and specific environmental regulations can pose challenges to implementing this small-scale farming system. Furthermore, resistance from the surrounding environment or family members may also arise due to negative perceptions about the cleanliness or orderliness of the cultivation area.